2002
DOI: 10.1271/bbb.66.1641
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Reactive Oxygen Species and Photon Emission from a Browned Product

Abstract: The properties of photon emission arising from a browned product were investigated. The photon intensity of the browned product was proportional to the absorbancy at 420 nm, and was influenced by the amino acid structure. The fluorescence spectrum showed similar compounds in the browned product to be related with this photon emission. Superoxide and hydrogen peroxide contributed highly to this photon emission, and several redox compounds enhanced the photon intensity at appropriate concentrations. Our work sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Second, a method employing spectroscopic detection of the reduced Cu + complex that formed after the reduction of Cu 2+ by the antioxidants (PAO assay) (de Martino et al ., ) was applied. To measure the radical and reactive oxygen scavenging capacity, a 2,2‐diphenyl‐1‐picrylhydrazyl (DPPH) assay, the third method, and a chemiluminescence system (XYZ system) (Yoshiki et al ., ; Iida et al ., ), the forth method, were used.…”
Section: Introductionmentioning
confidence: 99%
“…Second, a method employing spectroscopic detection of the reduced Cu + complex that formed after the reduction of Cu 2+ by the antioxidants (PAO assay) (de Martino et al ., ) was applied. To measure the radical and reactive oxygen scavenging capacity, a 2,2‐diphenyl‐1‐picrylhydrazyl (DPPH) assay, the third method, and a chemiluminescence system (XYZ system) (Yoshiki et al ., ; Iida et al ., ), the forth method, were used.…”
Section: Introductionmentioning
confidence: 99%
“…Besides quantum technologies, COSPLI may find applications in exploring some new region of ultra-weak signals [40], like agriculture [41], food chemistry [42] and biomedicine [43]. For example, it has been reported that neuronal activity has correlation with ultra-weak photon emission (UPE).…”
Section: Iccdmentioning
confidence: 99%
“…Evidence clearly indicates that photon emissions from rice cells elicited by N-acetylchitosaccharide are closely associated with generation of ROS, together with regulation by Ca signaling and protein phosphorylation (21). Prior reports relate phosphates to bioelectrostatic involvement (3), ROS to cell signaling (22), and biophotons to ROS (23,24).…”
Section: Metal Ions: Cell Signaling Electron Transfer Ros Oxidativmentioning
confidence: 99%